Studies on nitric oxide (No), citrulline-no cycle enzmes, arginase, glutamine synthetase and oxidative status in anoxia (Hypobaric Hypoxia) and reperfusion states in rat brain - Mummedy, Swamy (Pusat Pengajian Sains Perubatan, 2012)
Nitric oxide is postulated to be involved in the pathophysiology of neurological disorders due to hypoxia/ anoxia in brain due to increased release of glutamate and activation ofNmethyl- D-aspartate receptors. Reactive oxygen species have been implicated in pathophysiology of many neurological disorders and in brain function. To understand their role in anoxia (hypobaric hypoxia) and reperfusion (reoxygenation), the nitric oxide synthase, argininosuccinate synthetase, argininosuccinate lyase, glutamine synthetase and arginase activities along with the concentration of nitrate /nitrite, thiobarbituric acid reactive substances and total antioxidant status were estimated in cerebral cortex, cerebellum and brain stem of rats subjected to anoxia and reperfusion. The results of this study clearly demonstrated the increased production of nitric oxide by increased activity of nitric oxide synthase. The increased activities of argininosuccinate synthetase and argininosuccinate lyase suggest the increased and effective recycling of citrulline to arginine in anoxia, making nitric oxide production more effective and contributing to its toxic effects. The decreased activity of glutamine synthetase may favor the prolonged availability of glutamic acid catising excitotoxicity leading to neuronal damage iii anoxia and reperfusion. The increased formation of thiobarbituric acid reactive substances and decreased total antioxidant status indicate the presence of oxidative stress in anoxia and reperfusion. The increased arginase and sustained decrease of GS activity in reperfusion group likely to be protective.